The Algerian banking system and the challenges of financial globalization - Abdelkader ‎ Haffai (Dirassat Journal Economic Issue, 2018)
Globalization is a phenomen that stands as one of the manifestations of the late twentieth century; it has left its effects on various policies, whether economic, social, political, cultural, etc. And since capital is the most affected areas, the institutions based on banking activity is required to be familiar with in terms of adoption of the methods of financial governance and gradual use of protection of the banking system and protecting them from being a hotbed of dirty money. In this context, the Algerian banking system is requiered to adapt to these challenges, both at the legislative level and organizational or informational one since banking is active in a risk environment